Experimental Research on the Effect of CVT Roller and Spring Parameters on Metic Motorcycle Performance - Purnomo, Bagiyo Condro Purnomo Condro; Farhan Aulia Rahman, Muhammad; Biantoro, Wahyu; Waluyo, Budi (Borobudur Engineering Review, 2023)
The current development of vehicle transmission technology aims to reduce vehicle energy consumption by increasing its performance. Continuously variable transmission (CVT) is an automatic transmission system that is often used in vehicles today. Meanwhile, replacing CVT rollers and springs can affect transmission efficiency, fuel consumption, and overall vehicle performance. So this research aims to explore the impact of replacing roller and spring components on the CVT on engine performance and confirmed by changes in CVT temperature. This research was carried out using a metic motorcycle, by measuring the performance values of the motorcycle in the form of vehicle torque and power using a dynamometer, apart from that the CVT temperature was also measured. The research results show the potential for increasing Torque and Power by using increased roller mass and spring constants. Apart from that, there is an increase in CVT temperature due to the use of an increased spring constant, this shows the potential for wear.